SECONDARY ENGLISH LANGUAGE TEACHER’S PERCEPTIONS OF STUDENTS DIFFICULTIES IN LEARNING VOCABULARY FACED BY INDONESIAN EFL STUDENTS - Baharudin, Baharudin; Saifullah, Saifullah; Alfadyah Zahra Hasan, Arini (English Education Department, 2024)
Many EFL (English as a Foreign Language) students are aware of the importance of having good English language proficiency. Yet, many have not had much success in learning the vocabularies. Vocabularies is one of the most important aspects in learning English. Why do students have difficulties in learning English vocabulary? What efforts do they need to solve the problem in learning English vocabularies? The purpose of this study is to investigate the difficulties that hinder secondary school EFL students from mastering English vocabularies based on secondary English language teachers’ perceptions. The respondents of this study are four English subject teachers who teach English at SMP N 1 Buton. The English teachers were chosen as respondents because they had the most insight into their students' performance and the difficulties, they encountered in learning English vocabulary. The questionnaire, which served as the primary research tool, was employed to gather data on the EFL teachers' perceptions regarding the difficulties faced by their secondary EFL students in learning English vocabulary, and what efforts these EFL teachers should make in teaching vocabulary learning effectively to students. The results showed that the main difficulties or problems for students in learning vocabulary were related to students’ lack of motivation, limited teaching materials, lack of English exposure, and inadequate learning facilities. Regarding the EFL teacher's efforts in improving students’ English vocabulary was done by approaching interactive learning variations using the help of digital learning media that adapts to the development of the current era to improve students English vocabulary. This highlights that students’ motivation is the main problems for EFL students, with teaching material and English exposure also showed other factors that hinders them from mastering English vocabulary. Therefore, it suggests that new teaching and learning strategies should be introduced to address these challenges in English vocabulary learning.